Tau as a fluid biomarker of concussion and neurodegeneration - Iftakher Hossain; Kaj Blennow; Jussi P Posti; Henrik Zetterberg (Concussion)
Concussion is predominant among the vast number of traumatic brain injuries that occur worldwide. Difficulties in timely identification, whether concussion led to neuronal injury or not, diagnosis ...